Increasing frequency of extremely severe cyclonic storms over the Arabian Sea. Issue 12 (December 2017) - Murakami, Hiroyuki; Vecchi, Gabriel; Underwood, Seth
Abstract In 2014 and 2015, post-monsoon extremely severe cyclonic storms (ESCS)—defined by the WMO as tropical storms with lifetime maximum winds greater than 46 m s− 1 —were first observed over the Arabian Sea (ARB), causing widespread damage. However, it is unknown to what extent this abrupt increase in post-monsoon ESCSs can be linked to anthropogenic warming, natural variability, or stochastic behaviour. Here, using a suite of high-resolution global coupled model experiments that accurately simulate the climatological distribution of ESCSs, we show that anthropogenic forcing has likely increased the probability of late-season ECSCs occurring in the ARB since the preindustrial era. However, the specific timing of observed late-season ESCSs in 2014 and 2015 was likely due to stochastic processes. It is further shown that natural variability played a minimal role in the observed increase of ESCSs. Thus, continued anthropogenic forcing will further amplify the risk of cyclones in the ARB, with corresponding socio-economic implications. Post-monsoon season severe cyclonic storms were first observed over the Arabian Sea in 2014 and 2015. Highresolution modelling reveals their increased frequency can be attributed to anthropogenic forcing, and not natural variability.